Synthesis and characterization of UHMWPE composite fabrics treated with bis-diazirine crosslinker and silica/PEG shear thickening fluid - Mahshid Mahbod; Stefania F. Musolino; Amir Nazemi; Jeremy E. Wulff; Reza Vaziri; Abbas S. Milani (Composites Part C: Open Access, 2024)
This study focuses on investigating the mechanical behavior of a set of new chemically-treated crosslinked Ultra-High Molecular Weight Polyethylene (UHMWPE) plain-weave fabrics with varying areal densities, and impregnated with a shear thickening fluid (STF). The evaluation of the materials performance included tensile, bias-extension (shear), puncture, and drop tower tests under low rates of loading. For comparison purposes, three different sample groups were considered: untreated fabrics, crosslinked fabrics, and crosslinked fabrics with STF. The STF impregnation was composed of fumed silica nanoparticles (NPs) suspended in a polyethylene glycol (PEG) medium. Both the individual and combined effects of the chemical crosslinking and STF impregnation on the UHMWPE fabrics were explored. Additionally, the impact of strain rate on the tensile and shear behavior of various material groups was examined. The findings revealed that the addition of the crosslinker and shear thickening fluid significantly improves the puncture resistance of the base UHMWPE fabric, by as high as 92 %. The energy absorption and specific energy absorption of the UHMWPE fabric also increased up to 55 % and 16 %, respectively, with the addition of both STF and crosslinker.